2015
DOI: 10.3389/fnins.2015.00487
|View full text |Cite
|
Sign up to set email alerts
|

A Transgenic Rat for Investigating the Anatomy and Function of Corticotrophin Releasing Factor Circuits

Abstract: Corticotrophin-releasing factor (CRF) is a 41 amino acid neuropeptide that coordinates adaptive responses to stress. CRF projections from neurons in the central nucleus of the amygdala (CeA) to the brainstem are of particular interest for their role in motivated behavior. To directly examine the anatomy and function of CRF neurons, we generated a BAC transgenic Crh-Cre rat in which bacterial Cre recombinase is expressed from the Crh promoter. Using Cre-dependent reporters, we found that Cre expressing neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
118
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 71 publications
11
118
3
Order By: Relevance
“…Cell-type specific studies have shown evidence for the involvement of several genetically defined CeA neurons in aversive behaviors such as defensive responses and anxiogenesis (Andero et al, 2014; Han et al, 2015; Haubensak et al, 2010; Isosaka et al, 2015; Li et al, 2013; McCall et al, 2015; Pomrenze et al, 2015; Sanford et al, 2017). However, despite early evidence suggesting the involvement of the CeA in appetitive behaviors (Galaverna et al, 1993; Gallagher et al, 1990; Parkinson et al, 2000; Ritter and Hutton, 1995) and more recent activation studies demonstrating a modulatory role of the CeA in appetitive behaviors (Cai et al, 2014; Robinson et al, 2014; Seo et al, 2016), how appetitive behavior integrates into a structural and functional model of amygdala has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-type specific studies have shown evidence for the involvement of several genetically defined CeA neurons in aversive behaviors such as defensive responses and anxiogenesis (Andero et al, 2014; Han et al, 2015; Haubensak et al, 2010; Isosaka et al, 2015; Li et al, 2013; McCall et al, 2015; Pomrenze et al, 2015; Sanford et al, 2017). However, despite early evidence suggesting the involvement of the CeA in appetitive behaviors (Galaverna et al, 1993; Gallagher et al, 1990; Parkinson et al, 2000; Ritter and Hutton, 1995) and more recent activation studies demonstrating a modulatory role of the CeA in appetitive behaviors (Cai et al, 2014; Robinson et al, 2014; Seo et al, 2016), how appetitive behavior integrates into a structural and functional model of amygdala has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…This also appears to involve an interaction with CRF, since anxiety produced by CRF injections into the lateral ventricles was absent in prodynorphin knockout mice or in mice pretreated with norBNI (Bruchas et al, 2009, Land et al, 2008). Supporting an interaction between CRF and dynorphin, roughly 60–75% of CRF neurons in the rat and mouse CeA co-express dynorphin (Marchant et al, 2007, Kim et al, 2017, Pomrenze et al, 2015). Nothing is known about this interaction in primates.…”
Section: Resultsmentioning
confidence: 98%
“…Both species contain many CRF neurons in the paraventricular hypothalamus (PVN), CeA, and bed nucleus of the stria terminalis (BNST), but extended amygdala CRF neurons exhibit anatomical differences. CRF neurons in mouse CeA are found anteriorly, whereas in rat they cluster in the posterior portion of the CeA (Asan et al, 2005, Pomrenze et al, 2015, Sanford et al, 2017). The lateral capsular subregion of the CeA, which contains serotonergic inputs in both species, has a dense CRF fiber plexus in mice that is absent in rats, providing an anatomical basis for interspecies differences in CRF-serotonergic interactions in the CeA (Asan et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the ventromedial nucleus of the hypothalamus and the pontine parabrachial nucleus provide moderate enkephalinergic afferents to the CeA (Poulin et al, 2006). Intrinsic amygdalar enkephalinergic neurons, that are known to be distinct from amygdalar CRF neurons (Drolet et al, 2001; Reyes et al, 2008; Van Bockstaele et al, 2010; Reyes et al, 2011; Andero et al, 2013; Kravets et al, 2015), may play a role in the local circuit regulation of amygdalar neurons as there exists significant evidence describing such intrinsic connections in the CeA (Haubensak et al, 2010; Ciocci et al, 2010; Pomrenze et al, 2015). Potential opioidergic afferents to the BLA could also originate from local axonal arborizations of intrinsic enkephalinergic pyramidal neurons originating from the BLA (McDonald et al, 2005; Pitkanen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%